Intraperitoneal rupture of the bladder due to inapparent abdominal trauma - Cassinelli, Daniel (Cirugía del Uruguay, 2021)
We have had a case of intraperitoneal rupture of the bladder due to inapparent traumatism. The paper states the difficulty in establishing the diagnosis due to a state of inebriation and to the slight repercussion. It shows the coexistence of bladder repletion due to inebriation and traumatism. The paper gives an account of the treatment and correct postoperatory evolution